The role of programme evaluation in organisational decision-making about management and leadership development - Voller, Shirine (Cranfield University, 2010)
A number of models of evaluation exist in the education and training domain, yet most are rarely cited in studies of the effectiveness of management and leadership development. Given the vast sums of money that continue to be invested by organisations in management development, we must assume that organisations are perceiving value and that this is identified, in the main, through processes other than formal evaluation. Relatively little attention has been paid to how organisations use evaluation models and data, and a specific challenge has been raised about the usefulness of evaluation models in informing decisionmaking. To begin to address this challenge, this study set out to document the role of programme evaluation in organisational decision-making about management and leadership development. Eight customised programmes aimed at “high flyers” and middle to senior managers were studied. In each case, the way in which decisions were made and the role played by evaluation were explored from multiple stakeholder perspectives. The study found that programme evaluation did contribute to decisions made about management and leadership development, but only to a limited extent, and only to a subset of decisions. Central to the organisational decision-making process were stakeholder preferences and experience. This included anecdotal data and impressions gained informally by key stakeholders who came into direct contact with a programme and its participants. External influences, unrelated to the programme itself, were also important. Given these findings, it is suggested that there may be value in re-framing evaluation as part of an Evidence-Based Management (EBMgt) approach. EBMgt recognises the contribution of four elements of evidence to effective decision-making. Currently, decision-making about management and leadership development programmes does not draw fully on all four elements. Evaluation, both context-specific and casting light on external evidence, is underutilised, resulting in potentially sub-optimal decisions. Thus, future research to explore how to better integrate these elements would be valuable.